THE INFLUENCE OF SHARIA, SUKUK AND SHARIA MUTUAL FUNDS TO NATIONAL ECONOMIC GROWTH YEAR 2011-2019 - Luqman, Luqman (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
This research aims to test and analyze the influence of sharia stocks, Sukuk, and sharia funds against national economic growth. This type of research is associative with a quantitative approach. The data used in this research is secondary data obtained from the report of the stock value of Sharia, sukuk and sharia funds published in the Financial Services Authority (OJK) and the Indonesian economic growth publication data from the central statistic (BPS) period 2011 to 2019. The sampling technique used is the Probability Sampling method, which is to fetch the quarterly data from the years 2011 to 2019 which results in a sample of 32 samples. Data analysis is done by using statistics with SPSS tools. Based on the results of data analysis by using test-T is known that partial shares of Sharia and sukuk influential significant and positive to the growth of national economic and sharia funds partially no significant effect on national economic growth. While based on the results of data analysis using Uji-F is known that simultaneously shares of Sharia, sukuk, and sharia funds have a significant and positive influence on national economic growth.